ACHIEVING SUSTAINABLE TOURISM IN A GLOBALIZED WORLD - Tanil, Gamze (European Scientific Journal, ESJ, 2015)
Over time an ever increasing number of destinations have opened up and invested in tourism development, turning modern tourism into a key driver of socio-economic progress through export revenues, the creation of jobs and enterprises, and infrastructure development. Globally, as an export category, tourism ranks fourth after fuels, chemicals and food. For many developing countries it is one of the main sources of foreign exchange income and the number one export category, creating much needed employment and opportunities for development. However, there is no economic activity without costs. Tourism generates environmental, social, and cultural costs, which are not totally inevitable. The crucial motto of the sustainable development is development to meet the needs of the present without compromising the ability of future generations to meet their own needs. So, the crucial question is how to foster sustainable tourism which respects local cultures, environment, society and economy all of which are already under the pressure of impacts of globalisation. This article investigates this question thoroughly with an aim to offer easily applicable methods and strategies to tourism professionals. In order to do that, this article starts with presenting the costs and benefits of globalisation and tourism, then moves on to the presentation of the methods for sustainable development. Finally, it discusses the strategies and methods to keep up the current level of growth of the tourism industry while preserving the environment, the earth, local societies and cultures, which is an important mission of today’s globalised world